2016: USM CONSOLIDATES ITS POSITION AS A GLOBAL UNIVERSITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 14 January 2016 – In view of its successes thus achieved so far, Universiti Sains Malaysia (USM) is now focusing its efforts on becoming a Global University (UG).